Oral and perioral lesions - Swinyer, Leonard J., 1940-; American Academy of Dermatology. Committee on Audiovisual Education; Institute for Dermatologic Communication and Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1979)
(Critical) This program illustrates various pathological conditions involving the oral and perioral areas. Identification is provided on a key accompanying the slides. Previous knowledge of the entities is needed to facilitate identifying the pathology. The visual quality is variable, but by and large, it is of good quality. To serve as an instructional program for a naive audience, more didactic information is necessary. The program is recommended with reservations as a review of dermatologists, dentists, and oral surgeons
Rating: Recommended
Review date: Jan. 1982
Reviewer: Association of American Medical Colleges (AAMC)
Learning method: Support
Collected by Leonard J. Swinyer
Keywords: Mouth Neoplasms